Some facets of human resource management in the industrial organizations in Bulgaria after the privatization - Kiril Dimitrov (Economic alternatives, 2008)
The current article presents a part of the results of empirical survey, conducted to explore the condition of human resource management in the privatized industrial organizations in our country. The generated results may assist the surveyed companies' managers in their pursuit of high level organization's competitiveness after Bulgaria's unification with the European Union members.
Keywords: O34; A12; K0; M0; 330; human resource management; industrial enterprises; “employer – employee” relationship